Uganda : Report on the Observance of Standards and Codes; Data Module, Response by the Authorities, and Detailed Assessment Using the Data Quality Assessment Framework. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This Report on the Observance of Standards And Codes (ROSC) on data module for Uganda provides an assessment of Uganda's macroeconomic statistics against the recommendations of the General Data Dissemination System (GDDS) complemented by an assessment of data quality based on the IMF's Data Quality Assessment Framework. This ROSC data module contains the main observations covering four macroeconomic data sets, namely national accounts, the consumer price index (CPI), government finance statistics (GFS), and balance of payments (BOP). It also provides an overview of the dissemination practices compared with the GDDS.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet